Orthoptera assemblages associated with macrophytes of floodplain lakes of the Paraná River - Capello, Soledad (2013)
Orthoptera assemblages associated with macrophytes of floodplain lakes of the Paraná River. The Orthoptera assemblage composition varies considerably, depending on habitat type. This study examines the spatiotemporal relationship between plant diversity, hydrometric level, environmental variables and the Orthoptera richness and abundance in floodplain lakes connected permanently or temporarily with the main channel of the Paraná River. The grasshoppers were collected fortnightly (April 2006–May 2007). A total of 17 species were recorded and classified according to their frequency of occurrence in constant (7), accessory (4), or accidental (6) species. In the two lakes, the greater species richness and abundance was recorded in summer, thereby coinciding with the highest water level of the Paraná River. The most significant correlation between the orthopteran richness and abundance was with the water level. The aquatic plant richness was significantly different between the lakes, but the vegetation was dominated by Eichhornia crassipes (Mart.) Solms. (Liliales, Pontederiaceae). The lake, which was connected permanently, presented the highest values of diversity and abundance, proving to be a more diverse assemblage. The beta diversity was higher in the temporary connected lake than in the permanently connected one. The orthopterans assemblages were different between the lakes, Cornops aquaticum and Tucayaca gracilis were the species that contributed more to the level of dissimilarity. C. aquaticum was more representative in the lake temporarily connected, while T. gracilis in the permanent connected one. The water level of the Paraná River and the connectivity of the floodplain lakes play an important role to explain the abundance and richness of their orthopteran assemblages.